Toward Open-World Software: Issues and Challenges. - Baresi, Luciano; Di Nitto, Elisabetta; Ghezzi, Carlo (Computer (00189162), 2006)
The article discusses the issues and challenges in open-world software development. The authors reflect that the closed-world assumption that the boundary between environment and system is known and unchanging has been the basis of traditional software development. This basis of assumption is no longer suited to the present's unpredictable open-world settings. Open-world settings demand techniques that let software react to changes by self-adapting its behavior and self-organizing its structure. The authors suggest that research must be directed to provide techniques and tools to realize this open-world software. They mention that polymorphism and dynamic binding offers the first step in developing system that runs in an open-world.